2008
DOI: 10.1037/h0100460
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of aggression with behavioral programming that includes supplementary contingent skin-shock.

Abstract: Behavioral treatment of aggression with contingent skin shock (CSS) has been investigated in relatively few studies and never with cognitively typical individuals. We evaluated CSS during a 3-year period with 60 participants, half to two-thirds of whom functioned at normal or near-normal cognitive levels. Sixty individual charts, arranged in a multiple baseline across participants display, reveal clearly the effectiveness of the treatment. When end-of-baseline data were compared with end-of-treatment data, CSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In addition, very few studies collected information on whether CESS was acceptable to those implementing or overseeing the treatment (e.g., families, staff). Finally, as with Duker et al (2002), several studies included other treatments in combination with CESS (e.g., differential reinforcement of other behavior, physical guidance, verbal reprimands, functional communication training), making it difficult to evaluate the isolated effects of CESS on behavior change (e.g., Israel et al, 2008Israel et al, , 2010Williams et al, 1994;Williams, Kirkpatrick-Sanchez, & Iwata, 1993).…”
Section: Methodological Concernsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, very few studies collected information on whether CESS was acceptable to those implementing or overseeing the treatment (e.g., families, staff). Finally, as with Duker et al (2002), several studies included other treatments in combination with CESS (e.g., differential reinforcement of other behavior, physical guidance, verbal reprimands, functional communication training), making it difficult to evaluate the isolated effects of CESS on behavior change (e.g., Israel et al, 2008Israel et al, , 2010Williams et al, 1994;Williams, Kirkpatrick-Sanchez, & Iwata, 1993).…”
Section: Methodological Concernsmentioning
confidence: 99%
“…As noted above, several studies demonstrated an immediate and significant reduction in challenging behavior and a reduction in the use of restraint and fewer staff injuries (e.g., Israel et al, 2008). However, there have been several negative side effects indicated as well.…”
Section: Adverse and Unwanted Side-effectsmentioning
confidence: 98%
See 3 more Smart Citations